Therapeutic Potential of Gut Microbiota in Hypertension: Mechanisms of Immune Modulation and Inflammation - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2025)
Emerging evidence links gut dysbiosis to numerous ailments, including hypertension and metabolic diseases. Multi-omics techniques have revealed that hypertensive individuals exhibit distinct alterations in their gut bacterial composition and metabolite profiles. The gut microbiome influences blood pressure through several mechanisms. For instance, microbiota-derived metabolites can have beneficial effects, such as those from short-chain fatty acids (SCFAs), or detrimental ones, like trimethylamine N-oxide (TMAO). These molecules modulate downstream signaling pathways via G protein-coupled receptors or direct immune cell activation. Furthermore, dysbiosis can compromise the gut epithelial barrier, leading to systemic inflammation that activates key regulatory pathways like the renin-angiotensin-aldosterone system (RAAS), the autonomic nervous system, and the immune system. Given these connections, the gut microbiome is a promising therapeutic target for hypertension. This review explores the potential of modulating the gut microbiota to manage blood pressure, focusing on the underlying mechanisms of immune modulation, inflammation, and microbial metabolites. By focusing on the 'how' rather than the 'what' of hypertension, it is identified that immune-mediated inflammation is orchestrated by the gut microbiota, as the core mechanism driving the disease. Gut dysbiosis is triggered by environmental factors like high-salt diets, perpetuates a pro-inflammatory state that undermines the efficacy of conventional antihypertensive drugs and contributes to treatment-resistant hypertension. Consequently, modulating the gut microbiota through targeted interventions, including dietary fiber, probiotics, and fecal transplantation, might represents a critical evolution in treatment. This approach moves beyond managing symptoms to directly correcting the inflammatory dysfunction at the heart of the disease, offering a powerful strategy to complement existing therapies.KEYWORDS: hypertension, inflammation, gut microbiota, metabolite